1988
DOI: 10.1093/nar/16.24.11645
|View full text |Cite
|
Sign up to set email alerts
|

Sequence organization and cytological localization of the minor satellite of mouse

Abstract: A complete 120 bp genomic consensus sequence for the mouse minor satellite has been determined from enriched L929 centromeric sequences. The extensive sequence homology existing between the major and minor satellite suggests an evolutionary relationship. Some sequences flanking the minor satellite has also been identified and they provide insight into centromeric DNA organization. Isotopic in situ hybridization analysis of the minor satellite to mouse L929 and Mus musculus metaphase spreads showed that this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
117
1
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(128 citation statements)
references
References 26 publications
9
117
1
1
Order By: Relevance
“…7a) (44). Complex A was formed by CENP-B in 0.5 M NaCl nuclear extracts obtained from mouse cells, and the CENP-B box is also conserved in mouse minor satellite DNA (22,26,48). Considering this evidence, it is possible that the interaction between CENP-B and CENP-B boxes in centromeric satellite DNA might carry an important function, for example, assembling the centromeric satellite DNA.…”
Section: Discussionmentioning
confidence: 92%
“…7a) (44). Complex A was formed by CENP-B in 0.5 M NaCl nuclear extracts obtained from mouse cells, and the CENP-B box is also conserved in mouse minor satellite DNA (22,26,48). Considering this evidence, it is possible that the interaction between CENP-B and CENP-B boxes in centromeric satellite DNA might carry an important function, for example, assembling the centromeric satellite DNA.…”
Section: Discussionmentioning
confidence: 92%
“…The order of such homology is sorghum/maize Ͼ sorghum/wheat Ͼ sorghum/oats Ͼ sorghum/rice. The ␣-satellite in primates and the minor satellite in mouse (18,20) are the only repetitive DNA elements that were demonstrated to be related to centromeric function. However, the centromeric region of fission yeast chromosomes contains several classes of repetitive DNA sequences (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Given the repetitive nature of this region, PCR techniques cannot be reliably quantitative or give information about the size of the transcripts. We therefore performed Northern blot analysis on total RNA isolated from the above-cited murine cells, in different growth and differentiation conditions, using the minor satellite 120-bp unit (6) in both orientations as a probe. We showed that minor satellites were indeed transcribed, as previously reported for other cell types (18,19), as two long, yet barely detectable, 2-and 4-kb precursor transcripts (Fig.…”
Section: Minor Satellite Transcripts Accumulate As Small Rnas In Murimentioning
confidence: 99%
“…The mouse genome contains two classes of centromeric repetitive sequences, termed major and minor satellites, organized in largely uninterrupted blocks of tandem repeats. Cytological detection of these clusters shows distinct localization, major satellites being associated with pericentromeric regions, whereas minor satellites were detected at the primary constriction of condensed mitotic chromosomes (6,7). The nature of protein complexes recruited to these satellite repeats also appears to be distinct.…”
mentioning
confidence: 96%